Clean, Safe and Healthy Mobility through Non-Technical Measures - Linking Individual and Public Decision Levels. - Doll, Claus; Hartwig, Johannes (My University, 2013)
The project "Economic aspects of non-technical measures to reduce traffic emissions", funded by the German Environmental Agency, had as an objective to assess measures, i.e. non-technical options to reduce the emissions of motorized road traffic. The focus of the study is on the effect of measures to reduce emissions and the associated consequences for the private sector and the economy as a whole. This study aims to provide an objective basis for the debate about the commercial and social consequences of more sustainable traffic behavior on the part of both individuals and companies. The assessment was performed using two tools, one focusing on an individual-based level whereas the other (ASTRA-D) is a macro-economic model.
Keywords: Verkehr; Verkehrsverhalten; Verkehrspolitik; Verkehrsmittelwahl; ÖPNV; Modellierung; Externe Kosten; Gesundheit; Verkehrssicherheit; Umweltbelastung